MICROTOPONYMS AS COGNITIVE MAPS: MENTAL REPRESENTATION OF URBAN SPACES - Yoldoshkhonov Javohirbek (Bright Mind Publishing, 2025)
This article explores microtoponyms — informal, small-scale place names — as cognitive maps that shape how individuals perceive, navigate, and emotionally relate to urban spaces. While previous research in toponymy has largely focused on official or administrative place names, this study emphasizes the cognitive and cultural significance of microtoponyms as elements of mental cartography. Drawing on theories from cognitive linguistics, ethnolinguistics, and linguistic landscape studies, the article examines how microtoponyms function as anchors of collective memory, spatial orientation, and social identity. Through a comparative case study of two culturally distinct urban centers—Tashkent (Uzbekistan) and London (UK)—the research utilizes ethnographic interviews, cognitive mapping tasks, and linguistic analysis to uncover how residents use microtoponyms in everyday navigation. The findings reveal that these names reflect not only spatial logic but also deep-rooted cultural narratives and emotional attachments. The study contributes to a broader understanding of urban toponymy by demonstrating how microtoponyms serve as culturally embedded cognitive tools, offering insights into how people mentally organize and communicate their lived environments.
Keywords: Microtoponymy, cognitive maps, spatial cognition, mental representation, cultural memory, linguistic landscape.